2015
DOI: 10.1016/j.joi.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the number of authors of a publication, its citations and the impact factor of the publishing journal: Evidence from Italy

Abstract: Empirical evidence shows that co-authored publications achieve higher visibility and impact. The aim of the current work is to test for the existence of a similar correlation for Italian publications. We also verify if such correlation differs: (i) by subject category and macro-area; (ii) by document type; (iii) over the course of time. The results confirm world-level evidence, showing a consistent and significant linear growth in the citability of a publication with number of co-authors, in almost all subject… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 45 publications
5
44
2
1
Order By: Relevance
“…Within the field of information systems, for instance, total number of co-authors of a study is positively correlated with the number of citations received by that study [ 17 ]. This positive effect of total number of co-authors on citations has also been found across scientific fields in Italy [ 18 ], in the field of demography [ 19 ], as well as in Russian molecular biologists [ 20 ].…”
Section: Introductionmentioning
confidence: 60%
“…Within the field of information systems, for instance, total number of co-authors of a study is positively correlated with the number of citations received by that study [ 17 ]. This positive effect of total number of co-authors on citations has also been found across scientific fields in Italy [ 18 ], in the field of demography [ 19 ], as well as in Russian molecular biologists [ 20 ].…”
Section: Introductionmentioning
confidence: 60%
“…Hence, citation analysis helps researchers to obtain a preliminary idea about the articles and research that has an impact in a particular field of interest and it deals with the examination of the documents cited by scholarly works [29,30]. In addition, there are various bibliometric studies has been evaluated based on different metrics and applications such as forecasting emerging technologies by using bibliometric and patent analysis [31], multiple regression analysis for Japanese patent case [32], medical innovation using medical subject headings [33], based on region or countries [34][35][36], number of authors [37,38] and a bibliometric analysis based on number publications and cited references [39].…”
Section: Introductionmentioning
confidence: 99%
“…As we have noted above, additionally we aim to control for factors that might affect citation. Here we took account of Baldi ( 1998 ) whose work indicated the importance of the following in influencing citation positively: the count of authors (a point on which Abramo and D’Angelo ( 2015 ) also agree); length of article; and relevance of the article to “recent work” (Baldi 1998 , p. 841) in influencing citation. The variable we constructed to describe recent work was a dummy variable coded one if the paper included any one of the top four keywords in use in the set of papers under examination.…”
Section: Methodsmentioning
confidence: 99%